Arte y simbolismo - Pérez-rubín, Carlos (Arte, Individuo y Sociedad, 2008)
This article presents a thorough study of perhaps, from the speculative viewpoint, the most interesting fresco mural painted by Raphael Santi, one of the most excellent Italian Old Masters, whose praises have not ceased to be sung by connoisseurs in the near five centures elapsed since his decease. He was held to be a child prodigy and eventually turned out an extrensive and admirable output of masterìeces but, regrettably, his life was cut short when he was in his prime. The interest awakened by this particular painting, which is deemed to be “the epitome of the Italian High Renaissance”, focuses not only on its splendid pictorial and aesthetical merits but also on the richness of an explicit and implicit or underlying sybolism, which entails phylosophico-metaphysical messages of Neoplatonic derivation from Greek sources but to a large extent of Oriental origin.